Advantages of using sequential loading/degradation steps for the anaerobic mineralization of long chain fatty acids - Pereira, M. A. (2004)
In this work, suspended sludge that was able to accumulate up to 4570±257 mg COD-LCFA/gVSS (83% of palmitic acid) was studied. The specific methanogenic activity, the tolerance of aceticlastic methanogens to oleic acid toxicity and the oleic acid biodegradation capacity, were assessed before and after allowing the mineralization of the biomass-associated LCFA. The capacity of the sludge to mineralize the associated LCFA was proven and the behavior of the sludge before and after that mineralization clearly suggested that sequential loading/degradation steps for the treatment of lipidic/LCFA based effluents have a potential interest.